STUDY OF ENVIRONMENTAL MANAGEMENT SYSTEM IMPLEMENTATION AT JONE SLAUGHTERHOUSE (RPH) - Ahmad Hadian Pratama Hamzah; Herman Herman; Nurhasanah Nurhasanah; Subekti Nurmawati (Universitas 17 Agustus 1945 Semarang, 2023)
Environmental Management System (EMS) is one of the tools that can be used in environmental management. Slaughterhouses (RPH) are facilities, where animals are slaughtered for consumption as food products. This practice aims to assess and identify the current suitability/conditions at Jone Slaughterhouse (RPH) to the implementation of the Environmental Management System from ISO clause 14001. Practice shows that there are several documented ISO 14001 clauses such as organization (clause 4), Leadership (clauses 5.1, 5.3), planning (clause 6.1.3), support (clause 7.1), and performance evaluation (clause 9.1.2).This practice aims to analyze and identify the current suitability / conditions at Jone Slaughterhouse (RPH) to the implementation of the Environmental Management System from ISO clause 14001 to the operations of RPH Jone.This practice is useful as a study and information material as well as a study for interested parties to take concrete steps or policies in the development of the slaughterhouse business (RPH) based on the ISO 1400 Environmental Management System